A Phone Pal to overcome social isolation in patients with psychosis-Findings from a feasibility trial. - Mariana Pinto da Costa; Kirat Virdi; Athanasia Kouroupa (PLOS Digital Health, 2024)
People with psychosis often experience social isolation due to stigma. Several volunteering programmes that exist in the community to support patients expect in-person meetings, requiring greater availability and commitment. This study investigated the acceptability and feasibility of remote volunteering over a smartphone for people with psychosis over 12 weeks, exploring its potential impact on both patients and volunteers. A total of 36 participants took part in the study. In the first phase, six participants were recruited in less than three weeks in London. All established contact with their match, and there were no study withdrawals. In the second phase, 30 additional participants were recruited in four weeks, across the United Kingdom. Most patients and volunteers reported that they primarily used audio calls to make contact, followed by text messages, WhatsApp messages and video calls. There were improvements in patients' scores of quality of life, self-esteem, social contacts and symptoms, and in volunteers' ratings of quality of life, physical activity, self-esteem, social comparison, and social distance towards people with mental illness. This study demonstrates that it is feasible, acceptable and safe to remotely connect volunteers and people with psychosis who are afar. Trial registration: ISRCTN17586238 (registration date: 28/09/2018).